DIAGNOSTIC AND THERAPEUTIC VALUES OF AMINO ACID COMPOSITION OF BLOOD AND AMINO ACID INDICES AS MARKERS OF ARRHYTMIAS OF ISCHEAMIC GENESIS AND CARDIOVASCULAR RISK IN PATIENTS WITH STABLE ISCHEAMIC HEART DISEASE ON THE BACKGROUND OF DIABETES MELLITUS TYPE - Belikova , J. (The Ukrainian Scientific Medical Youth Journal, 2017)
The purpose of the study was to determine the diagnostic value of the amino acid composition of blood (ACC) and its indices as markers of cardiac rhythm disturbances (СRD) and cardiovascular risk (CVR) in patients with stable coronary heart disease (CHD) in patients with type 2 diabetes mellitus (DM2) . Object and methods of investigation The data of examination of 51 patients with stable ischemic heart disease in the background of CD2 (30 men and 21 women, median ages -64, 2 years) and 22 patients with stable coronary heart disease without violations of carbohydrate metabolism were analyzed. 20 amino acids (AMC) and the relationships between them were determined, in which AMCs were combined by a competitive mechanism of transport into the cell. According to the results of holter ECG monitoring, patients with comorbid pathology were divided into 2 groups: with and without arrhythmias of ischemic genesis (AIG) of high grades. Results The Tau / Ala and Fen + Tyr / Met indices have high specificity (Sp) and positive predictive value (PPV) (93.9 and 95.1 and 93.9 and 95.1, respectively) at low sensitivity (Se ) and negative predictive value (NPV). The Tau and BCCA indices showed low Sp and PPV at high Se and NPV (89.9 and 86.7 and 84.6 and 86.5, respectively). The statistically significant correlation between the ASA indices and the parameters characterizing lipid (LO) and carbohydrate metabolism (VO), SDP, and cardiovascular risk (SSR) on the SMART scale (SMART RISK) were found. Conclusions Since none of the specified indicators demonstrated simultaneously high specificity and sensitivity to AIG, and correlation relationships with lipid and carbohydrate metabolism and AIG did not show a high and moderate strength of communication in all parameters, the indices should be applied in accordance with the research stage: Tau and ARCs are most suitable for screening purposes, Tau / Ala and Phen + Tyr / Meth are more suitable for the purpose of therapy and as a control of treatment.